2014
DOI: 10.1016/j.envres.2014.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Low-level mercury in children: Associations with sleep duration and cytokines TNF-α and IL-6

Abstract: There is a sizeable literature suggesting that mercury (Hg) exposure affects cytokine levels in humans. In addition to their signaling role in the immune system, some cytokines are also integrally associated with sleep behavior. In this cross-sectional study of 9–11 year old children (N = 100), we measured total blood Hg in whole blood, serum levels of tumor necrosis factor α (TNF-α) and interleukin 6 (IL-6), and objectively measured sleep and activity using actigraphy. Increasing blood Hg was associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The study of TNF-α and IL-6 levels in the blood serum of children aged 9 to 11 yr, an increase of Hg levels were associated with a shorter sleep duration and a lower TNF-α level. IL-6 was not associated with sleep or blood mercury (27). A crosssectional study of the population in Amazonian Brazil (28) demonstrated that the levels of proinflammatory cytokines IL-1, TNF-α and IFN-γ were significantly higher in mercury-exposed subjects and anti-nucleolar autoantibodies + (AN (o) A +) as compared to participants with lower mercury exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The study of TNF-α and IL-6 levels in the blood serum of children aged 9 to 11 yr, an increase of Hg levels were associated with a shorter sleep duration and a lower TNF-α level. IL-6 was not associated with sleep or blood mercury (27). A crosssectional study of the population in Amazonian Brazil (28) demonstrated that the levels of proinflammatory cytokines IL-1, TNF-α and IFN-γ were significantly higher in mercury-exposed subjects and anti-nucleolar autoantibodies + (AN (o) A +) as compared to participants with lower mercury exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Mercury exposure also results in changes in cytokine production. In children, mercury exposure has been found to be associated with reduced levels of TNF-alpha and shorter sleep duration [63]. One possible mechanism of sleep disruption by Hg is the effect on glutamate, which results in increased extracellular glutamate and a possible excitotoxic effect [64].…”
Section: Mercurymentioning
confidence: 99%
“…Another heavy metal as mercury induced effect on neuroimmune signaling, mercury exposure cause increase in TNF-α expression in hippocampus and cerebellum (test in prairie voles) (Thomas Curtis et al 2011 ). Interesting studies have been conducted by Gump et al 2014 . They showed that increasing blood Hg (9–11 children) was correlated with lower concentration of TNF-α in whole blood and shorter sleep duration.…”
Section: Cytokines In Milkmentioning
confidence: 99%